PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L.) Merill) DENGAN PEMBERIAN RHIZOBIUM DAN PUPUK UREA PADA MEDIA GAMBUT - INDAH PERMANASARI; MOKHAMAD IRFAN; ABIZAR ABIZAR (Jurnal Agroteknologi, 2014)
Soybean is legume plant that has ability to symbiosis with Rhizobium. This process produces nitrogen thus decrease the need of urea fertilizer. The purpose of current research was to investigate the effect of Rhizobium and urea dosage on growth and yield of soybean. The research was conducted in experimental field of Agriculture and Animal Science Faculty of State Islamic University of Syarif Kasim Riau, started from May until July, 2012. Peat soil media and soybean cv. Wilis were used in this study. Randomized Completed Block Design with two factorials and three replications was employed for experimental design, in which the first factor was the Rhizobium (with/without Rhizobium application) whereas the second factor was dosage of urea fertilizer (0, 75, 150 and 225 kg/ha, respectively). The following parameters were observed e.g. plant height, number, weight and diameter of root nodules, flowering time, age of harvest time, number of pods/plant, number of seeds/pod, weight of 25 seeds, weight of dry seed/plant, weight dry plant, weight dry root and colour of leaf. The result showed that Rhizobium application increased the number of pods/plant. Urea fertilizer with dosage of 225 kg/ha increased number of seeds/plant, weight of 25 seeds, weight of dry plant, and weight dry seed. Interaction between Rhizobium and urea fertilizer were significantly different to weight dry root.